Comparative Study of Sondgrass and Bracka’s Surgical Techniques for Hypospodias Repair - Yasir Arfat Memon, Rizwana Fazlani, Imran Ahmed, Kashan Qayoom Shaikh, Sadia Rasheed, Ghulam Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the outcomes of Bracka’s and Snodgrass techniques in hypospadias repair among the patients admitted at Liaquat University Hospital, Jamshoro. Methods: Prospective study was conducted at the plastic surgery unit, Liaquat University Hospital, Jamshoro from January 2018 to December 2019. All male children aged between 6 months-15 years, given consent of participation, having distal hypospadias and were not previously operated for hypospadias (primary cases) with chordee, good prepuce and wide urethral plate were included. The study was ethically approved from university ethical review committee and informed consent taken from the parents / guardians. Study participant children were divided in two equal groups according to the surgical technique used. Group I (Snodgrass procedure) and Group II (Bracka’s procedure). Pre and post-surgical examination of patients were performed to determine any complications and evaluate the cosmetic results. Results: Total 100 participating pediatric patients of Hypospadias were included in the study. The mean age of study participants was 3.4±2.2 years with age range between 6 months and 15 years. Statistically significant difference (p<0.05) between operative time and length of postoperative hospital stay of Group I and Group II. Urethrocutaneous fistula and meatal stenosis were observed as the most common postoperative complications in study participants. A statistically significant difference in complications between group I and group II (p<0.05). Conclusion: Bracka’s technique is more beneficial compared to Snodgrass in terms of urethral fistula. While due to meatal stenosis Snodgrass technique is much advantageous because of higher scar amount results after Bracka’s method. Keywords: Congenital abnormalities, Hypospadias, Postoperative Complications